Moral Education Values Based on Gau Satoto in Pajam South Kaledupa, Wakatobi, Southeast Sulawesi - Muh. Hamiruddin S. (Universitas Muhammadiyah Enrekang, 2023)
This research aims to know the historical background of the birth of Gau Satoto; to describe the background of the emergence of Gau Satoto-based moral education; to describe the values of Gau Satoto-based moral education in Pajam, South Kaledupa, Wakatobi.This research uses a qualitative approach with a case study research type. The data in this study were obtained through data collection techniques: observation, in-depth interviews and documentation. And data analysis techniques through the stages of data collection, data reduction, data presentation, and conclusion making.The findings of this study are: 1) Gau Satoto means the path to truth which originates from wise advice which is used as an ideology, used to run a system of government and social life with the aim of creating harmony, unity, mutual love among people. 2) The birth of Gau Satoto-based moral education in Pajam as wise advice to have a noble character in every joint activity of life. Gau Satoto's moral education is based on his existence as a guide to happiness in this world and in the hereafter. 3) The values of Gau Satoto-based moral education in Pajam, South Kaledupa, Wakatobi, Southeast Sulawesi, namely the Tadhe-Kedhe Dhi Killi values involve morals towards oneself including self-preservation, gratitude, obedience, discipline, habituation, and responsibility. Next is the Ponamis value, the Dhi Bannara Parakonta value and the Fila Dhi Barani/Filangaka Dhi Toto value including morals towards fellow human beings including the value of compassion, goodwill and evil, mutual cooperation, honesty, obedience to rules, trustworthiness, sticking to the truth , brave, determined. And the value of Saba'ane'e Dhi Kawasa Nu Moori, this value includes morals towards Allah SWT. includes the value of sincerity, trust, piety and remembrance.